Impact of physical activity on the progression of atherosclerosis in patients with antiphospholipid syndrome - Djokovic, Aleksandra; Stanisavljevic, Natasa; Matic, Predrag; Zivic, Rastko; Filipovic, Branka; Bozovic, Kristina; Banovic, Marko; Polovina, Marija; Pavlov Dolijanovic, Slavica; Stojanovich, Ljudmila (Medical Research, 2025)
Introduction: Antiphospholipid syndrome (APS) is linked to an increased risk of cardiovascular diseases due to the interplay between traditional risk factors and antibody-induced endothelial damage. Limited data exist on the level of physical activity (PA) in APS patients. This study aimed to analyze PA domains in Serbian APS patients and their association with atherosclerosis progression.Materials and Methods: Fifty-one APS patients (29 with primary APS (PAPS), mean age 44.0 ± 11.5, and 22 with APS/SLE, mean age 48.4 ± 11.7) completed the long form of the International Physical Activity Questionnaire (IPAQ), translated into Serbian. PA was categorized into leisure time, domestic activities, work-related, and transport-related domains, and classified as low, moderate, or high. Carotid Doppler ultrasound scans were performed to detect atherosclerotic plaques.Results: The total PA in a PAPS group ranged from 0 to 26.880 MET-minutes/ week and in sAPS from 0 to 19.200. Work-related and domestic activities had the highest scores, while leisure time PA was lowest. Most patients had low (37.3%) or moderate (43.1%) PA levels, with only 19.6% in the high PA category. No significant PA differences were found between PAPS and sAPS patients. However, PAPS patients were more likely to have high PA (27.6% vs. 9.1%), though not significantly. Patients with lower PA scores had a higher prevalence of carotid plaques, particularly for vigorous (p=0.001) and total PA (p=0.002).Conclusion: Younger Serbian APS patients predominantly exhibit low or moderate PA, especially during leisure time. Low PA strongly correlates with atherosclerosis progression, underscoring the need to promote physical activity in this population.
Keywords: antiphospholipid syndrome; atherosclerosis; physical activity